EVALUASI PENCAPAIAN PROGRAM KELUARGA BERENCANA DI PUSKESMAS KOTA BUKITTINGGI TAHUN 2019 - Widya Nengsih; Adis Fitriyana (HUMAN CARE JOURNAL, 2020)
Family planning is an action that helps couples to avoid unwanted pregnancies, get births, and determine the number of children in the family. It is known that the achievement of contraceptive use in the City of Bukittinggi has a number of productive couple  as many as 24,563 people, and the number of active family planningwas 13,781 (56.11%). The research objective is to evaluate the achievement of family planning programs in the City Health Center in Bukittinggi year 2018. This research was a qualitative research with evaluation study method. This research was conducted at the Health Center ofBukittinggi Cityon  July 5th -  August 15th 2018. The informants consisted of 4 heads of Health Center, 4 midwives holding a family planning program, and 8 users of family planning services. Data collection using in-depth interviews, then processed with the Miles and Huberman models.The results of the study revealed that there was enough quality of Human Resources in the implementation of family planning, and that adequate funds and facilities and infrastructure were sufficient. Inhibiting factors / constraints include lack of involvement of cadres, lack of support in using family planning, especially from husbands, and location of the Helath Center that are less strategic and difficult to reach the community. The expected output has not reached the target, in accordance with the findings in the field.